(untitled) (MAUSAM, 1976)
Trend in the minimum and maximum temperatures at Bombay airport has been examined for the period 1950-1974. Colaba temperatures have been taken for comparison. The study reveals that the mean daily minimum temperature at Bombay airport in creased due to rapid urbbnisation and industrialisation around the airport. The decreasing trend in mean minimum temperature during 1959 to 1963 was due to the increased air flow from E/NE direction as a result of cutting of hills, In the vicinity of the airport in these directions. The mean daily maximum temperature also show an increasing trend from 1962 on wards, due, to higher order influence of urbranisation as compared to that of industrialisation.